2018
DOI: 10.1074/jbc.ra117.000456
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor 21 (TCF21) promotes proinflammatory interleukin 6 expression and extracellular matrix remodeling in visceral adipose stem cells

Abstract: The visceral (VIS) and subcutaneous (SQ) fat pads are developmentally distinct white adipose tissue depots and contribute differently to inflammation and insulin resistance associated with obesity. The basic helix-loop-helix transcriptional regulator, transcription factor 21 (TCF21), is a marker gene for white adipose tissues and is abundantly expressed in VIS-derived adipose stem cells (ASCs), but not in SQ-derived ASCs. However, TCF21's role in regulating fat depot-specific gene expression and function is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…As reported in a study by Akama et al [91] they found that IL6 mediates the expression of Mmp13 and Timp1 in visceral fat derived-ASCs and the TCF21-dependent expression of Mmp2 and Col4a1 is IL6-independent. The basic helix-loop-helix transcriptional regulator, transcription factor 21 (TCF21), is a marker gene for white adipose tissues and is abundantly expressed in visceral-derived ASCs.…”
Section: Promotion Of Wound Healingmentioning
confidence: 52%
“…As reported in a study by Akama et al [91] they found that IL6 mediates the expression of Mmp13 and Timp1 in visceral fat derived-ASCs and the TCF21-dependent expression of Mmp2 and Col4a1 is IL6-independent. The basic helix-loop-helix transcriptional regulator, transcription factor 21 (TCF21), is a marker gene for white adipose tissues and is abundantly expressed in visceral-derived ASCs.…”
Section: Promotion Of Wound Healingmentioning
confidence: 52%
“…FAPs from HFD-fed mice were nonetheless qualitatively different, exhibiting elevated expression of specific adipocyte-related genes. Tcf21, a WAT marker (42), recently shown to be enriched in visceral adipose stem cells (38), was induced in FAPs with HFD feeding, as was Il6, a TCF21-regulated gene (38). HFD feeding also upregulated FAP-specific expression of Ucp1, corresponding with presence of scattered UCP1 + unilocular Figure 5-Isolated FAPs demonstrate obesity-induced fibrotic gene expression signature, with increased ex vivo proliferation and collagen deposition.…”
Section: Discussionmentioning
confidence: 93%
“…Those allocated for adipogenesis were cultured for 5 days (reaching full confluence), then switched to standard medium plus adipogenic cocktail (1 mg/mL insulin, 250 nmol/L dexamethasone, 10 mmol/L troglitazone, and 10 nmol/L triiodothyronine) for 7 days, and then switched to standard medium plus insulin (1 mg/mL) for 3 days. After each experiment, cells were fixed, blocked, and immunostained as previously described (38). For Ki67 staining, wash buffers and antibody diluents contained 0.2% Tween-20.…”
Section: Cell Culturementioning
confidence: 99%
“…TCF21 is expressed in epicardial progenitor cells that give rise to coronary artery smooth muscle cells and cardiac fibroblasts ( Nurnberg et al, 2015 ), the latter of which are a source of activated myofibroblasts in the infarcted heart ( Kanisicak et al, 2016 ). TCF21 is also a marker for white adipose tissue and is abundantly expressed in visceral fat-derived stem cells ( Akama and Chun, 2018 ). When we overexpressed TCF21 in FAP-high CAFs, our results indicated that TCF21 on its own can significantly dampen the ability FAP-high CAFs to promote gel contraction, invasion, chemoresistance, and in vivo tumor growth.…”
Section: Discussionmentioning
confidence: 99%